Assessment of the Effect of Business Innovation on Performance of Small and Medium Enterprises Supermarkets in Laikipia County, Kenya. - Kibet , Christine Chepkoech; Rintari, Nancy; Moguche, Abel (International Journal of Professional Practice, 2023)
Supermarkets form a significant component of retail, and therefore their growth is paramount. However, the performance of Kenyan supermarkets has experienced low performance concerns. The purpose of this study was to assess the effect of business innovation on performance of SMEs Supermarkets in Laikipia County. A descriptive survey research design was adopted and data was collected using questionnaires. The study target population was 200 respondents, from 9 supermarkets in Laikipia County. Slovin’s sampling formula was used to obtain 133 study population comprising supervisors and operation staff, who were selected using simple random method. Pre-testing of 10% of the sampled population was conducted in Magunas and Sayen supermarket in Meru County. Data was collected, sorted and coded, using SPSS software. Regression analysis used to test the hypotheses. Data was presented using in tables and explanations. Descriptive statistics such as frequency, percentage, and mean were used. The findings on performance revealed that 112(86%) respondents agreed on a mean of 4.1 that there was less turn-around time taken to replace stock on the shelves of the supermarket. However, 105(81%) disagreed on a mean of 2.4 that salaries of staff were paid on time. The study also established that business innovation had a 41% percent variation in performance. The study concluded that there was still resistance by the management to fully incorporate innovation and collaborate the operations of the supermarket effectively. Additionally, supermarkets relied on walk-in customers instead of vigorously conducting e-marketing campaigns to improve sales. Therefore, the management should undergo training on relevance of various business innovations and models with a view of incorporating them in the management of the supermarket. The staff should also be encouraged to market the supermarket’s products using online platforms.